Examining the Relationship between Social Support and Interracial Divorce in Louisiana. (August 2021) - Grether, Scott T.; Jones, Antwan
This study examines how social support is related to divorce among interracial couples in Louisiana. Using longitudinal, couple-level data from the Marriage Matters Survey, we analyze how measures generally associated with divorce (e.g., couple-level characteristics, individual characteristics, and premarital events) operate similarly within interracial and same-race unions, and whether these measures moderate the relationship between social support and divorce among interracial couples. Results indicate that interracial marriages are not more likely to divorce than same-race unions, and lacking social support does not predict divorce for any marriage. Irrespective of marriage type, premarital counseling reduces the odds of divorce, while marriages with women who had more education than their husband and who cohabitated with someone other than their husband prior to marriage increase the likelihood of divorce. This study contributes towards understanding the mechanisms associated with interracial divorce and questions the claim that interracial marriages are less stable than same-race marriages.